Future readers: narrating the human in the Anthropocene. Issue 5 (29th July 2017) - Vermeulen, Pieter
ABSTRACT: This essay argues that the growing awareness of anthropogenic climate change and of the possibility of human extinction has begun to alter the very function of narrative; understood as a mode of knowledge, and as a technology through which cultural knowledge is archived in the present, narrative no longer only serves as a way of (cognitively) organising and emplotting human experience, but also as a way of (affectively) apprehending the end of possible human life. The essay develops this argument through a discussion of one of the most popular tropes in the Anthropocene imagination: that of a future reader who, in an imagined future, reads the remains of contemporary existence. Drawing on an archive of contemporary and of popular science writing, the essay argues that this future reader takes two different disciplinary forms: as a historian who chronicles historical errors that she, unlike us, is able to appreciate, or as an archaeologist who will be left to read mankind's geological footprint after its extinction. While the former, historical mode conforms to a traditional use of narrative, the second, geological one points up the anxieties, desires, and uncertainties besetting the anticipation of human extinction - here routed through the imagining of a radically nonhermeneutic and nonhuman form of registration.